2020
DOI: 10.3389/fgene.2020.00725
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Immune-Related Genes’ (IRGs) Signature Models in Cervical Cancer and Endometrial Cancer

Abstract: Cervical cancer and endometrial cancer remain serious threats to women's health. Even though some patients can be treated with surgery plus chemoradiotherapy as a conventional option, the overall efficacy is deemed unsatisfactory. As such, the development for new treatment approaches is truly necessary. In recent years, immunotherapy has been widely used in clinical practice and it is an area of great interest that researchers are keeping attention on. However, a thorough immunerelated genes (IRGs) study for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 74 publications
(81 reference statements)
0
23
0
Order By: Relevance
“…Low risk patients significantly benefited from chemotherapeutic and immunotherapeutic treatments. In addition to tumor-infiltrating immune cells, immune-related gene sets such as RIPOR2, DAAM2, SORBS1, and CXCL8 ( Mei et al, 2020 ), or LTA, TFRC, TYK2, DLL4, CSK, JUND, NFATC4, SBDS, FLT1, IL17RD, IL3RA, SDC1, PLAU ( Ding et al, 2020 ), were proposed as prognostic genes to stratify CESC patients. However, neither of these studies took co-expression of immune networks into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Low risk patients significantly benefited from chemotherapeutic and immunotherapeutic treatments. In addition to tumor-infiltrating immune cells, immune-related gene sets such as RIPOR2, DAAM2, SORBS1, and CXCL8 ( Mei et al, 2020 ), or LTA, TFRC, TYK2, DLL4, CSK, JUND, NFATC4, SBDS, FLT1, IL17RD, IL3RA, SDC1, PLAU ( Ding et al, 2020 ), were proposed as prognostic genes to stratify CESC patients. However, neither of these studies took co-expression of immune networks into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Giuseppina et al found that a decrease in lymphotoxin-ß production by tumor cells was associated with a loss of follicular dendritic cell phenotype and diffuse growth of follicular lymphomas [27]. Recently, the gene was found to be associated with immune infiltration of breast and endometrial cancer tumors [28, 29]. The analysis using the TCGA dataset showed that TNFRSF9 was altered in approximately 5% of cases of Cholangiocarcinoma, adrenocortical carcinoma (ACC) and lymphoid neoplasm diffuse large B-cell lymphoma (DLBC), with deep deletion being the dominant alteration (Supple.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have established an immune-related prognostic signature and a glycolysis-related gene signature in EC, which have provided the basis for predicting prognostic risk in EC patients. 14 , 15 Another study identified several transcription factors related to the prognosis of EC patients. 16 Nevertheless, a prognostic signature based on transcription factors to systematically and accurately evaluate EC prognosis is lacking.…”
Section: Introductionmentioning
confidence: 99%